Arzobispado de Manila archives a preliminary guide - Libang, Virginia D. (1979)
Arzobispado de Manila Archives: A Preliminary Guide attempts to record and organize 1,670 ecclesiastical bundles of documents dating between 1581 and 1963 available in the Archdiocese of manila Archives now housed in San Carlos Seminary, Guadalupe, Makati, Rizal. This checklist serves as a finding aid, a guide to, and an inventory of the manuscripts and unpublished documents, while at the same time it unearths the vast mass of historical materials and claims "continuing interest in bibliographic tools for historical source materials."